Development of a website based participatory communication management system between schools and parents to enhance the effectiveness of educational collaboration in elementary schools - Michael Alan Hirdi Pukada; Wahyudi; Sophia Tri Satyawati (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The increasing demand for effective school–parent collaboration in the digital era has highlighted the limitations of conventional communication practices, which are often characterized by one-way information flow, lack of structure, and limited parental engagement. This study aims to develop and evaluate a website-based participatory communication management system designed to enhance the effectiveness of educational collaboration in elementary schools. The research employed a Research and Development (R&D) approach using the ADDIE model, integrated with a sequential exploratory mixed methods design. Data were collected through observations, interviews, document analysis, and questionnaires involving 24 participants, including school leaders, teachers, administrative staff, and parents. Qualitative data were analyzed using the Miles and Huberman interactive model, while quantitative data were analyzed using descriptive statistics and pre-test–post-test comparisons with the support of SPSS. The findings indicate that the developed system, integrated with the SOFIA application, is highly valid, practical, and effective. The effectiveness of school–parent collaboration increased significantly from 59.44% (moderately effective) to 87.94% (highly effective), accompanied by improvements in communication transparency, parental involvement, and the quality of two-way interaction. These results demonstrate that a structured and participatory digital communication system can transform fragmented communication into a collaborative and transparent process. The study contributes theoretically by integrating participatory communication principles with digital system design and offers a practical model that can be adopted by schools to strengthen stakeholder engagement and educational outcomes.